Permalink Submitted by m_muller on August 14, 2016

So correct me if I'm wrong.
Can't we write Z = 1-1+1-1+1 as this?>>>>> (1+1+1+1+1+.....) - (1+1+1+1+1+1+....) = Z
All I did was pair up the positive 1's and the negative 1's and added them together.
If you assume that both sets of sums add up to infinity, their result would come out to be zero.
But, you can also look at what the sum of 1+1+1+1.... was proved to be. Which is -1/2. So in this sense,
(-1/2) - (-1/2) = (-1/2) + (1/2) = 0. So Didn't I just prove that the sum 1-1+1-1+1.... = 0?
If not, where is my mistake?

## 1-1+1-1+1... = 0

So correct me if I'm wrong.

Can't we write Z = 1-1+1-1+1 as this?>>>>> (1+1+1+1+1+.....) - (1+1+1+1+1+1+....) = Z

All I did was pair up the positive 1's and the negative 1's and added them together.

If you assume that both sets of sums add up to infinity, their result would come out to be zero.

But, you can also look at what the sum of 1+1+1+1.... was proved to be. Which is -1/2. So in this sense,

(-1/2) - (-1/2) = (-1/2) + (1/2) = 0. So Didn't I just prove that the sum 1-1+1-1+1.... = 0?

If not, where is my mistake?